2017
DOI: 10.1111/ajo.12634
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' experience of performing female pelvic examinations: Opportunities and barriers

Abstract: The majority of medical students have performed several pelvic examinations on real patients at graduation. Male gender and access being limited by midwives were the main barriers to performing female pelvic examinations. Medical curricula need to address these issues in the learning environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…The International Society of Ultrasound in Obstetrics and Gynaecology [15] recommend that a minimum of 100 transvaginal scans are required prior to proficiency, which may not be achievable during RANZCOG One such barrier may be trainee confidence, and participants reported poor confidence levels prior to training. The TRUSST programme resulted in improved confidence levels in participants performing a TVUS, and while confidence does not equate to competence, it can be a barrier to performing procedures, especially intimate ones [16]. Table 2 Real patient scanning experience pre-and post-training Although our study demonstrated improvement in scanning skill on the simulator, Tolsgaard et al [17] demonstrated a sustained improvement in scanning abilities on live patients 2 months following simulation training with clinical experience compared to clinical experience alone.…”
Section: Discussionmentioning
confidence: 54%
“…The International Society of Ultrasound in Obstetrics and Gynaecology [15] recommend that a minimum of 100 transvaginal scans are required prior to proficiency, which may not be achievable during RANZCOG One such barrier may be trainee confidence, and participants reported poor confidence levels prior to training. The TRUSST programme resulted in improved confidence levels in participants performing a TVUS, and while confidence does not equate to competence, it can be a barrier to performing procedures, especially intimate ones [16]. Table 2 Real patient scanning experience pre-and post-training Although our study demonstrated improvement in scanning skill on the simulator, Tolsgaard et al [17] demonstrated a sustained improvement in scanning abilities on live patients 2 months following simulation training with clinical experience compared to clinical experience alone.…”
Section: Discussionmentioning
confidence: 54%
“…The advantage of the simulation method is the ability to learn how to perform the correct examination before the start of clinical classes. There are papers presenting that 33% of medical graduates have never conducted a gynaecological examination [14]. According to patients, the consent or refusal of a vaginal examination was influenced by factors such as: gender (with a predominance of women), age (for the benefit of older students), less formal behaviour and past gynaecological examination experience [15].…”
Section: Patient Examinationmentioning
confidence: 99%
“…Many medical learners report high levels of discomfort performing genital exams [5255], though simulation and working with standardized patient volunteers appear to lessen their discomfort. Pelvic exam competencies tend to focus on performing a vaginal and bimanual exam, as well as a pap smears.…”
Section: Myth #4: Clinicians Are Well Trained To Identify the Morpholmentioning
confidence: 99%